MORPHOLOGICAL AND ANATOMICAL RESEARCH OF LEAVES OF FEIJOA SELLOWIANA BERG - N. N. Vdovenko-Martynova; N. V. Kobylchenko; T. I. Blinova; H. M. Dodova (Фармация и фармакология (Пятигорск), 2015)
Feijoa leaves gathered from Feijoa sellowiana Berg. of Myrtaceae family on the Black Sea coast of the Caucasus were the object of this research. Establishment of morphological and anatomical features for diagnosis of feijoa leaves was the purpose of this work. Using macro- and microscopic analysis methods we have determined external and microdiagnostic features which can be used for development of authenticity of the feijoa leaves active parts.